Hepatoprotective Effects Of Papaya Leaves Extract (Carica Papaya L.) With Increased Dose: A Study Of Total Bilirubin Levels Of Wistar Rats That Given Paracetamol - Adhani Rihhadatul 'aisy; Kanti Ratnaningrum; Dyah Mustika Nugraheni (Universitas Ahmad Dahlan, 2021)
Incorrect use of paracetamol can cause overdose and cause liver damage. Papaya leaves is a plant that has the potential as hepatoprotective because it contains flavonoids, saponins, tannins, alkaloids, triterpenoids and vitamin E. The aim of this study was to prove the hepatoprotective effect of papaya leaf extract on the total bilirubin levels of Wistar rats given paracetamol. This research was conducted using a post test only control group design method and used 24 wistar rats grouped by simple random sampling into negative control (K-), positive control (K +), treatment 1 (PI), and treatment 2 ( PII). PI and PII groups were given papaya leaf extract 75 mg / kgBB rats / day and 150 mg / kgBB rats / day for 7 days. On days 5 to 7, the K +, PI, and PII groups were given paracetamol 600 mg / kgBW rats / day. Samples were taken on day 8 and total bilirubin levels were measured on day 9 then analyzed using One Way Anova and Post Hoc LSD test. There are significant differences in all groups based on the results of the One Way Anova test with p value= 0.000. The results of the LSD Post Hoc test showed significant differences in the K- group with K + (p = 0,000), K- with PI (p = 0.027), K + with PI (p = 0,000), K + with PII (p = 0,000), PI with PII (p = 0.004), and there was no significant difference between the K- and PII groups (p = 0.397). There was a hepatoprotective effect of papaya leaf extract on Bilirubin total levels in Wistar rats treated with paracetamol.